MODEL SINKRETISME ISLAM DAN KEJAWEN: KAJIAN HISTORIS-FILOSOFIS ATAS SERAT SASANGKA JATI - Abdullah Safiq (UIN Raden Mas Said Surakarta, 2019)
This study aims to examine the model of Islamic syncretism and variants ofKejawenteachings in Indonesia. Using a qualitative approach, based on historical-philosophical data analysis of the Sasangka Jatimanuscripts,completed within-depth interviews and observations on the living and religious practices of the Pangestufollwoers in Tulungagung, East Java, the results of the study indicate that there is a pointof similarities and differences between the essence of